PENGARUH PENERAPAN PERATURAN PEMERINTAH NO. 46 TAHUN 2013 TERHADAP TINGKAT PERTUMBUHAN WAJIB PAJAK UMKM DAN PENERIMAAN PPH PASAL 4 AYAT (2) (Studi Kasus pada KPP Pratama Malang Selatan) - Astri Corry Novita Dolok Saribu; Akie Rusaktiva Rustam (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
On July 1, 2013, government has authenticated the PP No. 46 Year 2013 representating the MSMEs tax expenses. In order to help the middle and small industrial economics activity, the government give the taxation facility to small scale Taxpayer (MSMEs) with the tax final rate 1% which imposed to the shares of circulation bruto up to Rp 4,8 bilions a year. This research aimed to describe the implementation of MSMEs tax expenses based on PP No. 46 Year 2013 and its contribution to PPh Pasal 4 Ayat (2) in the work region of Tax Service Office Pratama South Malang. This research used a descriptive method. The results of this research showed that the average contribution of PP No. 46 Year 2013tax for the revenue of PPh Pasal 4 Ayat (2) during the five months since the implementation of PP No. 46 Year 2013 is amounted to 6.51% with criteria very less. Although the monthly amount of MSMEs tax revenue continues to increase. While the growth rate of the amount of taxpayers PP No. 46 Year 2013 is continuing to increase every month. Keywords : PP No. 46 Year 2013, MSMEs, PPh Pasal 4 Ayat (2), Contribution